ANALISIS PELUANG KERJASAMA ANTARKABUPATEN DI KAWASAN BUNTOK-TANJUNG-TANAH GROGOT (KAWASAN BUNTAGO) - Prasetya, Hermawan (Jurnal Sains dan Teknologi Indonesia, 2008)
Cooperation development between regencies in Buntago Area (Buntok-Tanjung-Tanah Grogot) has been signed five year ago, but there is no significance realization. The aim of this article is to analyse the opportunities of cooperation in those area by comparison analysis, network and of suply-demand analysis.The result indicated that there are some opportunities to develop economic activities mainly in agricultural sector, services and mining. The result also indicated the opportunties to use high school building and its facilities together, optimizing a port in Tanah Grogot as outlet, and labor management cooperationamong the regencies.